2005
DOI: 10.1016/j.febslet.2005.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Grifolin, a potential antitumor natural product from the mushroom Albatrellus confluens, inhibits tumor cell growth by inducing apoptosis in vitro

Abstract: Grifolin is a natural biologically active substance isolated from the fresh fruiting bodies of the mushroom Albatrellus confluens. Here, for the first time, we describe a novel activity of grifolin, namely its ability to inhibit the growth of tumor cells by the induction of apoptosis. Grifolin strongly inhibited the growth of tumor cell lines: CNE1, HeLa, MCF7, SW480, K562, Raji and B95-8. Analysis of acridine orange (AO)/ethidium bromide (EB) staining and flow cytometry showed that grifolin possessed apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 26 publications
3
44
0
1
Order By: Relevance
“…The activities of two types of cyclins (cyclin D and cyclin E), Cdks (cyclin-dependent kinases 2, 4 and 6), and Cdks inhibitors are necessary for entering from the G1 phase into S phase of the cell cycle (Weinberg, 1989). Thus, most of bioactive substances from natural products have been reported to exert their anticancer activity by blocking cell cycle progression and triggering tumor cell apoptosis (Chang et al, 2004;Ye et al, 2005;Hsieh et al, 2006). Youn et al (2008) confirmed that I. obliquus water extract (IWE) previously used for treating cancers and digestive system diseases could selectively and significantly inhibited the viability and proliferation, and induced apoptotic cell death in human hepatoma HepG2 cells, while this effect was not found in the human immortalized non-tumor cell line.…”
Section: Involving In the Arrest Of Cell Cycle In Cancer Cellsmentioning
confidence: 78%
“…The activities of two types of cyclins (cyclin D and cyclin E), Cdks (cyclin-dependent kinases 2, 4 and 6), and Cdks inhibitors are necessary for entering from the G1 phase into S phase of the cell cycle (Weinberg, 1989). Thus, most of bioactive substances from natural products have been reported to exert their anticancer activity by blocking cell cycle progression and triggering tumor cell apoptosis (Chang et al, 2004;Ye et al, 2005;Hsieh et al, 2006). Youn et al (2008) confirmed that I. obliquus water extract (IWE) previously used for treating cancers and digestive system diseases could selectively and significantly inhibited the viability and proliferation, and induced apoptotic cell death in human hepatoma HepG2 cells, while this effect was not found in the human immortalized non-tumor cell line.…”
Section: Involving In the Arrest Of Cell Cycle In Cancer Cellsmentioning
confidence: 78%
“…Inhibition of the growth of tumor cells by inducing of apoptosis and causing cell-cycle arrest [71,72] …”
Section: Mushrooms Bioactive Compound(s) Effects Referencesmentioning
confidence: 99%
“…Prenylphenols are a class of natural products. A number of phenolic compounds have been isolated from Albatrellus ovina, including the novel neogrifolin derivatives 3-hydroxyneogrifolin, 1-formylneogrifolin and 1-formyl-3-hydroxyneogrifolin along with grifolin (Ye et al, 2005) and neogrifolin (Nukata et al, 2002;Yuen-Nei Cheung et al, 2005) (Dekermendjian et al, 1997) and suillin (Liu et al, 2009). These compounds have been shown to play important physiological roles, including antioxidant activity, cholesterol metabolism regulation, antibacterial activity, anti-tumor activity and anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%